SPORT HYPNOSIS: EGO STATE DALAM MEREDUKSI ANXIETY ATLET TAE KWON DO (Studi Kasus pada Atlet PPOPD Tae Kwon Do Kota Salatiga) - Guntur Ratih Prestifa Herdinata Guntur Ratih Prestifa Herdinata; Mona Saparwati Mona Saparwati; Noer Indah Aprianti Noer Indah Aprianti (Jurnal Inovasi Penelitian, 2022)
Sport Hypnosis or Sports hypnosis refers to the use of hypnotherapy with athletes to improve sports performance. Every athlete must feel the mental turmoil, the mental that usually arises is anxiety. Anxiety or anxiety can arise during practice or during matches, and during the COVID-19 pandemic. The purpose of this study was to determine wheter the implementation of sport hypnosis : ego state could reduce the anxiety of taekwondo athletes in Salatiga This study uses a qualitative approach with comparative descriptive analysis. The data used in this study through the results of observations, interviews and documentation of objects and informants.The results of this study obtained information that exercise of sport hypnosis : ego state uses a combination of techniques commonly used in transactional analisys. After going through seeral stage of sport hypnosisi : ego state, it was proven to be able to reduce the level of anxiety in taekwondo PPOPD athletes in Salatiga. It can be seen that by reducing the level of anxiety in athletes, it is able to improve the performance of athletes wich is marked by an increase in the achievement of taekwondo PPOD athletes in Salatiga. Ego state therapy or ego state counseling is expected to add insight regarding counseling techniques that can be developed in a variety of problems faced by athletes, especially taekwondo PPOPD athletes in salatiga.